Yellow fever: risk disease in the americas - Loayza-Alarico, Manuel (2018)
Yellow fever is one of the oldest recognizedinfectious diseases, both in the old world(Africa) and in the new world (the Americas).It is an acute febrile illness of short duration,transmitted by mosquitoes and caused by theyellow fever virus. It is enzootic and does nothave specific treatment, but it can beprevented by vaccination. The clinicalmanifestations varies from asymptomaticforms or moderate febrile disease (90%) offavorable evolution to severe forms withmassive bleeding with a lethality up to 50% ofhepatic, renal and cardiac involvement.1 The yellow fever virus exists in nature in twocycles of transmission: a wild one in whichthe Haemagogus mosquito and non-humanprimates intervene and another urban oneinvolving man and the Aedes aegyptimosquito. The jungle form is that it isfrequently reported.2 However,periurbanization risk is being observed inurban areas of cities.   DOI: 10.25176/RFMH.v18.n2.1280